Índice de confort postquirúrgico en pacientes intervenidos de artroplastia total de rodilla con el uso del navegador en el hospital de Clínicas Pichincha. - Soto Toledo, Alexander Nicolay (2014)
The present research on "Comfort Index Intervenidos Postsurgical Patients in Total Knee Arthroplasty Using the Navigator in the Hospital de Clínicas Pichincha" was performed in order to evaluate the use of this technology as a surgical method applicable to patients with gonarthritis Tricompartmental GIV. This descriptive study was conducted on 40 of the 120 patients operated on ATR with navigator usage during the period from October 2011 to July 2013, postoperative comfort with the implementation of the WOMAC score and its direct relation was determined correction of varus / valgus angular defects, postoperative recovery time, time taken for surgery and navigation; and involvement in the learning curve. The results gave comfort postsurgical satisfaction 55%, Optimal mechanical axis (± 3 °), time taken for navigation 15 to 30 minutes a learning curve that averages 26 surgeries, so it is concluded that this type of surgery affects good and excellent results in both quality of life and functional capacity, being a useful tool for this type of surgery.